Parametric Study on Water Based Photovoltaic Thermal Collector - Mohd Rosli, Mohd Afzanizam; Mat, Sohif; Ruslan, Mohd Hafidz; Sopian, Kamaruzzaman (WSEAS Press, 2013)
This paper presents the simulation study on the water based photovoltaic thermal (PV/T). The study based on the variation of material and dimensions of the water tubes of absorber. A commercial photovoltaic (PV) has been used for the study and some of the parameter referred on the available technical paper. It showed the best performance of the thermal efficiency can achieve 49%. In this cases, the water tubes with diameter 25 mm x 20 mm square shape with 65 mm gap obtained highest thermal efficiency.